The use of interactive storytelling, cartoon animation and educational gaming to communicate the biblical message to preschool children - Van der Merwe, Dirk (HTS teologiese studies, 2020)
This article focuses on how biblical content and spiritualities can be communicated, probably more effectively, to (late) preschool children by using information technology, which has already been implemented successfully for years in secular and religious environments. Because children enjoy listening to stories, watching cartoons and playing every day, the approach in this research will be to propose a particular construct to communicate biblical content to preschool children. This construct comprises interactive storytelling, cartoon animation and educational gaming, which constitute a trilogy for teaching biblical content and principles to preschool children. This should be done interactively. These three approaches have become fundamental designs and presentations in child education. Churches, Christian nurseries and other Christian educators, in general, are encouraged to develop computer programs according to the construct and strategy proposed in this article for the teaching of the Gospel to late preschool children. The approach in this article will be, firstly, to examine and explore the religious orientation of preschool children and, secondly, to validate and propose how computer technology can be implemented to communicate the biblical content to preschool children via the trilogy of interactive storytelling, cartoon animation and educational gaming in an uninterrupted experience.Contribution: This article argues that the use of interactive storytelling, cartoon animation and educational gaming should be used consecutively and uninterruptedly to communicate the biblical message to preschool children. This is probably the most effective way to keep the attention of these children and to affect their conduct.